Atividades investigativas e história da ciência : tendências em potencial para promover o pensamento crítico - Santos, Fernando Carvalho (2018)
The literature on science education points out that the history of science, by means of Contextual Approach (AC) and Investigative activities (AI) contribute to making the most challenging classes and helping to develop reflective critical thinking of the students. These themes have been studied in the research project that sought to investigate how workshops built and validated by licenciandos members of the Institutional Program of initiation into teaching, based on Contextual Approach and activities Investigative approaches, can help to mobilize critical thinking skills in Basic school students. You will find in the literature authors who argue that these trends are potential for the development of critical thinking, what if configured as a hypothesis of this work. As central study, we decided to treat as a research object the implementation of a workshop dealing with the history of electricity that has been applied in public schools. Data collection was performed through audiovisual instruments and written records collected in applications. Data were analyzed according to the content Analysis, using the aid of WEBqda software, which is a tool for video and audio analysis. The study followed two steps, the first consisted in examining an instrument that sought to bring together the goals of AC and AI with the skills of critical thinking. The second, proposed to investigate what critical thinking skills are potentially mobilized students who suffered the PIBID didactic proposal action. The results with the instrument approach point out that there's a narrowing between the goals of the Contextual Approach and Investigative activities with the skills of critical thinking, this claim was raised after lifting in the literature and enhanced with the responses of the subjects who responded the instrument approach. Already regarding the analysis of didactical interventions, the data indicate that there is the mobilisation of capabilities of thought in the area of clarification elementary, being manifest perspectivel "capabilities focus on an issue" and "analyze arguments". In this way, the work comes to contribute to teaching science asking professionals thinking methodologies with a view to promoting the development of critical thinking.